Knowledge of legal rights as a factor of refugee and asylum seekers’ health status: a qualitative study - Tara C Pilato; Faten Taki; Kaitlyn Sbrollini; Amanda Purington Drake; Brian Maley; Stephen Yale-Loehr; Jane L Powers; Natalya N Bazarova; Aparajita Bhandari; Gunisha Kaur (BMJ Open)
Objectives To examine health behaviours of refugees and asylum seekers, in relation to their knowledge of public benefits and legal rights.Design Qualitative study, utilising an open-ended, semi-structured interview guide to ensure information-rich data collection. Thematic content was analysed using qualitative research software.Setting Participants were drawn from the Weill Cornell Center for Human Rights (WCCHR) in New York City, a single-center, human rights clinic with a globally representative patient population. All interviews were conducted at the Weill Cornell Medicine Clinical and Translational Science Center, a multidisciplinary space within an urban academic medical center.Participants Twenty-four refugees and asylum seekers currently living in the greater New York City area. Eligible participants were 18 years of age or older and had previously sought services from the WCCHR. The recruitment rate was 55%.Primary and secondary outcome measures Themes and concepts in participants’ health, knowledge, perceptions of and experiences with accessing healthcare and public benefits programmes.Results Twenty-four participants represented 18 countries of origin and 11 primary languages. Several impediments to accessing healthcare and public benefits were identified, including pragmatic barriers (such as prohibitive costs or lack of insurance), knowledge gaps and mistrust of healthcare systems.Conclusions There is low health engagement by refugees and asylum seekers, as a result of multiple, complex factors impeding the ability of refugee and asylum seekers to access healthcare and other public benefits for which they are eligible—with resultant detrimental health effects. However, there is an opportunity to utilise novel approaches, such as digital technologies, to communicate relevant information regarding legal rights and public benefits to advance the health of vulnerable individuals such as refugees and asylum seekers.